Possible Selective Cytotoxicity of Vanadium Complex on Breast Cancer Cells Involving Pathophysiological Pathways - El-Shafey, Eman S.; Elsherbiny, Eslam S. (Anti-Cancer Agents in Medicinal Chemistry, 2019)
Background: Triple-Negative Breast Cancers (TNBC) are among the most aggressive and therapyresistant breast tumors. Development of new treatment strategies that target pathways involved in cancer cells resistance is an attractive candidate to overcome therapeutic resistance. Objective: To clarify the antitumor activity of [VO (bpy)2 Cl] Cl complex as a new therapeutic agent through studying the interplay between apoptosis, autophagy and notch signaling pathways. Methods: Proliferation of MDA-MB-231 cells and IC50 value of the vanadium complex were assessed by MTT assay. Flow cytometry was utilized to detect cell cycle distribution, apoptosis assay, LC3 levels and Acid Vascular Organelles (AVOs). Caspase 3 levels were detected by ELISA. Changes in Notch1 gene expression were assessed by real-time PCR. AVOs qualitative detection was assessed by a fluorescence microscope. Results: The growth of MDA-MB-231 cells was suppressed after treatment with [VO (bpy)2 Cl] Cl complex, in a dose-dependent manner. The affinity for apoptotic cell death induction was shown through the increase in the sub G0 peak, the percentage of early and late apoptotic phases, and the elevation in caspase 3 levels. The affinity for autophagic cell death induction was observed through the increase in the G0/G1 phase, G2/M arrest, the increase of AVOs red fluorescence and elevated LC3 levels. The affinity for notch pathway inhibition was shown through the suppression of Notch 1 gene expression. Conclusion: [VO (bpy)2 Cl] Cl complex could be a promising candidate as therapeutic agent targeting different therapeutic targets including apoptosis, autophagy and notch signaling pathways.
Keywords: vanadium complex